On tragedy and transcendence : a critical exposition of Donald MacKinnon and Rowan Williams in the context of a modern debate - Delport, Khegan (Stellenbosch : Stellenbosch University, 2019)
Thesis (PhD)--Stellenbosch University, 2019.